The characteristics of tropical nights in Poland in years 1951–2024 - Fojutowski, Michał (Quaestiones Geographicae, 2025)
Based on data on daily minimum temperatures, a detailed analysis was made of the occurrence of tropical nights (TNs), also known as hot nights, in 17 cities in the Polish territory between 1951 and 2024. TNs, i.e., those in which the minimum temperature does not fall below 20°C, are one of the extreme climatic phenomena occurring with increasing frequently at higher and higher latitudes. Polish provincial cities have seen an almost 10-fold increase in the number of TNs in the past decade compared to the 1950s. In 2021–2024, their sum was almost the same as in the entire decade 2001–2010. The time range of their occurrence throughout the year has also expanded, with TNs increasingly being recorded in June and even September in addition to July and August, which was not the case before 2015. The sequences of occurrence of hot nights at a single station have lengthened up to nine nights in a row. On 10 July 2024, a simultaneous occurrence of TN was recorded up to 10 of the 17 stations analysed. The rate of increase in the amount of TN at one station was 0.51/10 years, while at four others, it exceeded the value of 0.4/10 years. In 2015, Tmin ≥ 20°C was recorded up to 21 nights, while the last year without TN was 2008.